Promoting participatory rural development in the third world - Fernandez, Pepito R., Jr (Danyag : Journal of Humanities and Social Sciences, 2000)
Sustainable development, defined as a strategy for development that does not compromise the ability of future generations to meet their own needs, calls for the constructive and informed contribution of all the main actors in society, especially those who are left out in the discourse and benefits of development. This is the reason why participatory approaches have beccome increasingly widespread in development programs/projects, especially in the Third World. For participatory development to be relevant, it should be viewed in terms of the struggle of common people, in a hostile environment, to utilize their indigenous knowledge, ability and ingenuity in pursuing their own paths and interests. Aside from being a call for political action, participatory development is also an appeal for political controls to protect marginalized people and their natural resource base, and offer them a more favorable social context for their activities and innovations.